Mandala Art Therapy for Adults with Generalized Anxiety Disorder - Nurpratiwi, Galuh (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
Anxiety is a psychological problem that is often experienced by individuals, especially when facing stressful situations. One of the anxiety disorders is generalized anxiety disorder (GAD). This disorder can be characterized by excessive worry about something. Mandala art therapy is an art therapy by coloring a circle shape that contains various geometric symbols. The circular shape of the mandala can help reduce anxiety. Several studies have shown that mandala art therapy is widely used to treat generalized anxiety disorder, especially in the adult age group. It’s necessary to have systematic literature to find how the therapy plays a role. However, there has been no literature review regarding the effectiveness of mandala art therapy on generalized anxiety disorder in the adult age group. The purpose of this study is to determine the effectiveness of mandala art therapy in reducing anxiety in adult individuals with generalized anxiety disorder. This study is a systematic literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. The review was conducted using 12 journals determined through inclusion and exclusion criteria. The results obtained from the review show that mandala art therapy is effective in reducing anxiety in adult age groups. This is mainly because mandala art therapy combines art and therapy and has a therapeutic impact on generalized anxiety disorder in adults.Kecemasan merupakan masalah psikologi yang sering dialami oleh individu terutama dalam menghadapi situasi menekan. Salah satu gangguan kecemasan adalah generalized anxiety disorder (GAD).  Gangguan ini dapat ditandai dengan kekhawatiran berlebih terhadap suatu hal. Mandala art therapy merupakan terapi seni dengan mewarnai sebuah bentuk lingkaran yang terdapat berbagai simbol geometris didalamnya. Bentuk lingkaran pada mandala dapat membantu menurunkan kecemasan. Beberapa penelitian menunjukkan bahwa mandala art therapy banyak digunakan untuk mengatasi generalized anxiety disorder terutama pada kelompok usia dewasa. Untuk mengetahui bagaimana terapi tersebut berperan, maka diperlukan telah literatur sistematis. Namun, belum terdapat telaah literatur tentang efektivitas mandala art therapy secara khusus terhadap generalized anxiety disorder pada kelompok usia dewasa. Tujuan penelitian ini adalah untuk mengetahui efektivitas mandala art therapy untuk menurunkan kecemasan pada individu dewasa dengan generalized anxiety disorder. Penelitian ini merupakan telaah literatur sistematis dengan menggunakan protokol Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Review dilakukan dengan menggunakan 12 jurnal yang telah ditetapkan melalui kriteria inklusi dan ekslusi. Hasil yang didapat dari review menunjukkan bahwa mandala art therapy efektif dalam menurunkan kecemasan pada kelompok individu usia dewasa. Hal ini terutama karena mandala art therapy mengkombinasikan seni dan terapi yang memiliki dampak teraupetik generalized anxiety disorder pada individu dewasa.